2004
DOI: 10.1242/jeb.00818
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila CG8422encodes a functional diuretic hormone receptor

Abstract: SUMMARYDiuretic hormone 44 (DH) is a bioactive neuropeptide that mediates osmotic balance in a wide variety of insects through increases in cAMP. It is structurally similar to mammalian corticotrophin releasing factor (CRF)peptides. In the moth Manduca and the cricket Acheta,functional studies have shown that its cognate receptor (DH-R) is related to the mammalian CRF receptor. The Drosophila genome contains two genes(CG8422 and CG12370) orthologous to Manduca and Acheta DH-Rs. Here, we present multiple lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 41 publications
(42 reference statements)
5
67
0
1
Order By: Relevance
“…2). We previously reported that HEK293 cells transfected with DH44-R1 were two orders of magnitude more sensitive to DH 44 stimulation (Johnson et al, 2004), and repeated those experiments here and estimate a similar EC 50 value (5.12E-09 mol l -1 ) in the nanomolar range (Fig. 2).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…2). We previously reported that HEK293 cells transfected with DH44-R1 were two orders of magnitude more sensitive to DH 44 stimulation (Johnson et al, 2004), and repeated those experiments here and estimate a similar EC 50 value (5.12E-09 mol l -1 ) in the nanomolar range (Fig. 2).…”
Section: Resultssupporting
confidence: 84%
“…Previous studies have shown that DH 44 application to isolated tubules leads to elevated cAMP levels (Cabrero et al, 2002), and that the CG12370-related receptor, DH44-R1, encoded by CG8422, has been shown to stimulate this second messenger system as well (Johnson et al, 2004). Based on these observations, we tested for possible changes in this specific signaling component on HEK293 cells expressing CG12370.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations